Racial awareness, affect and sorting abilities: A study with preschool children - Guerrero, Silvia; Enesco, Ileana; Lam, Virginia (Anales de Psicología / Annals of Psychology, 2011)
Racial awareness and early attitudes was assessed in 50 majority-group Spanish children in two age groups (36-48 months and 60-71 months). A series of tasks in a semi-structured interview was administered to test the children‟s: Cognitive performance (classification task), sociocognitive measures (racial awareness by person description, social categorization, and self-identification) and affective measures (preferences and rejections). Children were further asked to make attributions about their mothers‟ racial preference and rejection. Overall, children‟s responses in person description and social categorization revealed that gender and colour of clothes had more salience in their perception than racial cues. In social affect tasks, children displayed a consistent in-group (White) bias, and a slight but noticeable out-group (Black) rejection. It was found that the cognitive performance measure predicted children‟s racial awareness and attitudes better than age did. The findings are compared to our further research, using the same procedure but in a multiracial context, and discussed in the light of theoretical approaches and the continuing sociodemographic transformations in Spain.